Amerikanskie vpečatleniă v tvorčestve Vladimira Korolenko = Impressions of America in the creative works of Vladimir Korolenko - Krylov, Văčeslav (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is devoted to the analysis of various artistic, documentary and journalistic works of Korolenko which are united by the American theme. Both the texts published and those unpublished during the writer's lifetime (travel notes, articles, correspondence) have been analyzed in the article. The analysis demonstrates that Korolenko's texts are not just ethnographic travel essays, but also a deep reflection on two images of the world - Russian and American, which contain an assessment of the pace of technological progress, of the ideals of freedom, as well as of the attitude towards pragmatism and individualism.
Keywords: Korolenko, Vladimir Galaktonowič (rosyjski pisarz; 1853-1921); literatura rosyjska; motywy amerykańskie; 19 w.; 20 w.